The Study of The Potential and Feasibility of Utilizing Biogas Energy as Power Plant at PT. BTSB Jember - Ahmad Aulia Reja; Sofia Ariyani; Aji Brahma Nugroho; Mokh. Hairul Bahri; Sutikno (JEECS (Journal of Electrical Engineering and Computer Sciences), 2023)
The limitation and scarcity of energy sources derived from fossil fuels necessitate the solution of utilizing renewable and replenishable alternative energy sources such as biogas. PT. BTSB (Biro Teknik Sinar Baru) is one of the companies in Jember Regency that has started utilizing biogas energy. However, the utilization of biogas is limited to cooking purposes only. Despite being used only for cooking, biogas can also be utilized as a source of electrical energy.Therefore, in this study, an analysis is conducted to determine the potential of biogas at PT. BTSB that can be utilized as a source of electrical energy. The first step taken in this research was to collect data from PT BTSB Jember regarding biogas which includes: number of cow, target of biogas volume, temperature in digester tank, pressure in digester tank, and methane (CH4) content in biogas. Based on this data, further calculations will be performed for mol of biogas, volume of biogas, electrical energy and power, conversion and production of energy and electrical power, and cost of energy production. Based on the research results, it is known that PT BTSB yields an average of 5.15 m³ of biogas per day and a potential of 57.53 kWh of electrical energy per day. With a cost of around Rp. 23,274,117 per day for each kWh, electricity from PT. BTSB’s biogas proves to be cost-effective. Thus, the biogas energy at PT. BTSB has the potential to be used as a biogas power plant.